Mycobacterium tuberculosis Microbiologic and Clinical Treatment Outcomes in a Randomized Trial of Immediate versus CD4+ -Initiated Antiretroviral Therapy in HIV-Infected Adults with a High CD4+ Cell Count - Chamie, Gabriel; Charlebois, Edwin D.; Walusimbi-Nanteza, Maria; Mugerwa, Roy D.; Mayanja, Harriet; Okwera, Alphonse; Whalen, Christopher C.; Havlir, Diane V. (Clinical infectious diseases, 2010)
In a prospective randomized, controlled trial in Uganda comparing the efficacy of antiretroviral therapy during tuberculosis therapy with the efficacy of tuberculosis therapy alone in HIV-infected patients with tuberculosis who have a CD4+ cell count >350 cells/µL, it was found that antiretroviral therapy did not accelerate microbiologic, radiographic, or clinical responses to tuberculosis therapy: 18% of participants had sputum smears positive for Mycobacterium tuberculosis after 5 months of tuberculosis therapy, despite having had negative culture results.
Keywords: Mycobacterium tuberculosis Microbiologic; High CD4+ Cell Count; HIV-Infected Adults; Clinical Treatment Outcomes